ESTIMASI ALIRAN SUNGAI BAWAH TANAH DI DAERAH DENGOK DAN NGREJOK WETAN GUNUNG KIDUL, MENGGUNAKAN METODE VLF-EM DAN VLF-EM-VGRAD - Anita, Febria; Purwantiningsih, Purwantiningsih (Sainstek : Jurnal Sains dan Teknologi, 2017)
A baseline river flow estimation has been conducted in the area of Duncok and Ngrejok Wetan Gunung Kidul, using VLF-EM and VLF-EM-VGRAD methods to find out VLF response of tilt angle mode. Interpretation is done from VLF and VLF-EM-VGRAD data of tilt angle and ellipticity to estimate underground stream that is interpreted qualitatively and quantitatively. Measurements were made on July 22-26, 2014. The data were processed by using uses MATLAB R2014a computational language. This qualitative interpretation is done by processing data filtered by Moving Average through Karous-Hajelt filter and Fraser filter so as to show the anomaly of underground conductive object. Of the two methods used, the most effective method is with VLF EM, it can be seen from the result of the Karous Hjelt filter shows the contrast resistivity in VLF EM compared to VLF-EM-Vgrad